2014
DOI: 10.1007/s11751-014-0187-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes following treatment of tibial non-union with circular frames

Abstract: The management of tibial non-union is challenging with protracted, often arduous, treatments. The purpose of this study was to assess patient-reported outcomes following treatment of tibial non-union in circular external fixators. Twenty-one patients with tibial non-unions who successfully completed treatment at a mean of 10.1 months (range 6–20) in a circular external fixator were sent questionnaires utilising the Enneking scoring system and Euroqol EQ-5D. There were 14 responses. The mean Enneking score was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…Five prior longitudinal studies on HRF systems were identified in the published literature [ 10 , 12 15 ]. The five studies are small relative to the current study and are not easily generalizable [ 10 , 12 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Five prior longitudinal studies on HRF systems were identified in the published literature [ 10 , 12 15 ]. The five studies are small relative to the current study and are not easily generalizable [ 10 , 12 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five prior longitudinal studies on HRF systems were identified in the published literature [ 10 , 12 15 ]. The five studies are small relative to the current study and are not easily generalizable [ 10 , 12 15 ]. Four of the prior studies were retrospective patient chart reviews with sample sizes ranging from 16 to 102 patients [ 12 15 ] and one of the prior studies was a patient survey (sample size of 14 patients) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations